1986
DOI: 10.32387/prokla.v16i63.1375
|View full text |Cite
|
Sign up to set email alerts
|

Die Mafia und das internationale Geldsystem

Abstract: In seinem Buch »La mafia imprenditrice« beschreibt der italienische Soziologe Pino Arlacchi die neuen Unternehmerqualitäten der Mafia. In der zweiten Hälfte der sechziger Jahre habe die Mafia einen qualitativen Sprung gemacht; aus den Mafiabossen seien schumpetersche Pionierunternehmer geworden. Er zeigt, daß die Mafia nicht etwa ein Relikt aus feudaler Zeit ist, sondern daß sich ihre Entwicklung als ursprüngliche Akkumulation unter spezifischen historischen Bedingungen interpretieren läßt. Darüber hin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

1994
1994
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 0 publications
0
13
0
1
Order By: Relevance
“…Considering the variety of qualitative research methods, all studies adopted appropriate research designs to examine, among the various objectives, also the recruitment into organized crime (item 2). Nevertheless, some studies offered limited detail on the source of information, as reported by item 3 (Albini, 1971; Arlacchi, 1983; Cressey, 1969; Gambetta, 1993; Hess, 1970/1973). Remarkably, these were all research monographs published until the early 1990s and offering broader analyses on the nature of organized crime.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Considering the variety of qualitative research methods, all studies adopted appropriate research designs to examine, among the various objectives, also the recruitment into organized crime (item 2). Nevertheless, some studies offered limited detail on the source of information, as reported by item 3 (Albini, 1971; Arlacchi, 1983; Cressey, 1969; Gambetta, 1993; Hess, 1970/1973). Remarkably, these were all research monographs published until the early 1990s and offering broader analyses on the nature of organized crime.…”
Section: Resultsmentioning
confidence: 99%
“…Eight qualitative studies considered the relation between age and involvement in organized criminal groups (Arlacchi, 1983; Arsovska, 2015; Cressey, 1969; Gordon, 2000; Hixon, 2010; Kemp et al, 2020; Radaelli et al, 2019; Van Koppen et al, 2010). The recruitment of younger individuals is frequently reported as a way of guaranteeing the intergenerational continuity of organized criminal groups (Arlacchi, 1983; Arsovska, 2015; Cressey, 1969; Hixon, 2010); However, late starters are not exceptional in organized crime recruitment, which can be related to opportunities coming from the social environment of adult individuals such as work and leisure activities, or to specific skills developed by individuals in late their life (Cressey, 1969; Gordon, 2000; Kemp et al, 2020; Kleemans & De Poot, 2008; Radaelli et al, 2019; Van Koppen et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ce phénomène est constaté dans les régions effectivement contrôlées par des organisations criminelles. On a même développé une théorie de la " mafia entreprise " en soulignant les analogies qui existent entre les organisations le mieux structurées et les entreprises légales 30 . Cette ingérence du criminel sur les marchés a notamment pour effet de perturber gravement le principe de concurrence : l'entrepreneur mafieux dispose de capitaux illimités et ne recourt pas à l'emprunt ; il s'affranchit largement des règles du droit social et syndical et surtout utilise la menace et/ou la violence pour décourager les concurrents.…”
Section: Les Activités Des Organisations Criminelles Et Paradoxalemen...unclassified